Study of Effect of Rat Embryonic Neural Tissue Peptides on Intracerebral Tumor Cells and Functional Activity of Peripheral Blood Mononuclears - Lisyanyy, M. I.; Belska, L. M.; Semenova, V. M.; Rozumenko, V. D.; Stajno, L. P. (Problems of Cryobiology and Cryomedicine, 2008)
The effect of embryonic brain peptides (EBP) of rats (E17) on viability of experimental cells of 101.8 strain glioma, human intracerebral tumors and functional activity of mononuclears of peripheral blood was studied. There was revealed that EBP of rats rendered a direct cytotoxic effect on cells of tumors and normalized the indices of spontaneous and stimulated production of superoxide radical of mononuclears of peripheral blood of neurooncological patients. The rate of this effect is of dose-dependent character.